The History of Iṣlāḥ al-Gazālī's Movement and Its Relevance to Contemporary Education Concept - Azwar, Azwar; Ikhsan, Muhammad (Journal of Islamic History and Manuscript, 2024)
The aim of this research is to understand the history of the islāḥ al-Gazālī movement and its relevance to the concept of contemporary education. This research method is qualitative-descriptive, using library research techniques and historical and sociological approaches. The findings indicate that al-Gazālī started the islāḥ movement by repairing himself first. Further, al-Gazāli diagnosed the problems faced by the Islamic community and found that the quality of society, good or bad, depended on the knowledge and credibility of scholars. Based on this diagnosis, al-Gazālī took improvement measures by including: producing a new generation of scholars and educators; designing educational systems and curricula in accordance with Islamic principles; reviving the mission of al-‘amr bi al-ma’rūf wa al-nahyī ‘an al-munkar; and fighting for social justice. Al-Gazālī's thoughts and actions played a crucial role in the process of reform and renewal in society, which produced the generation of Ṣalāḥuddīn al-Ayyūbī through reform of thought and education. In today's context, al-Gazālī's thought and movement suggest that the problem of Islam needs to be overcome from its root, namely "moral reform". The role of the scholar and the leader of the people are the two main elements that support the survival of the people, and both of these aspects should get serious attention.